2019
DOI: 10.1096/fj.201901205rr
|View full text |Cite
|
Sign up to set email alerts
|

PTEN deletion drives aberrations of DNA methylome and transcriptome in different stages of prostate cancer

Abstract: Phosphatase and tensin homolog located on chromosome 10 (PTEN) is a tumor suppressor gene and one of the most frequently mutated/deleted genes in human prostate cancer (PCa). However, how PTEN deletion would impact the epigenome and transcriptome alterations remain unknown. This hypothesis was tested in a prostate‐specific PTEN−/− (KO) mouse prostatic adenocarcinoma model through DNA methyl‐Seq and RNA‐Seq analyses. Examination of cancer genomic datasets revealed that PTEN is expressed at lower levels in PTEN‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 58 publications
(158 reference statements)
2
24
0
Order By: Relevance
“…Luminal cells of the prostate, which have been confirmed to be the prime origin of PC, generated tumors with stronger aggressivity under the condition of PTEN loss (31,32). Furthermore, PTEN was also reported to induce abnormal methylome and transcriptome of DNA (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminal cells of the prostate, which have been confirmed to be the prime origin of PC, generated tumors with stronger aggressivity under the condition of PTEN loss (31,32). Furthermore, PTEN was also reported to induce abnormal methylome and transcriptome of DNA (22).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, loss of PTEN expression indicated an unfavorable prognosis in PC (20,21). The anomaly of DNA methylome and transcriptome was caused by PTEN loss at different stages of PC (22). A previous study indicated that miRNA-1297 promoted cell proliferation via targeting PTEN in testicular germ cell tumors (23).…”
Section: Introductionmentioning
confidence: 96%
“…Previous work from our laboratory has shown that several dietary phytochemicals including curcumin, tocopherols, and PEITC significantly decrease the incidence of prostatic tumorigenesis and inhibit high-grade PIN in TRAMP mice via regulation of a series of cellular pathways including proliferation, apoptosis, cell cycle arrest, Akt signaling, and Nrf2/ARE-mediated antioxidative stress and detoxification. 20,[34][35][36][37][38][39][40] However, how the epigenome would be impacted during TRAMP PCa tumorigenesis and importantly how PEITC would affect the epigenome remain unknown. Here, we focused on exploring the transcriptomic and epigenomic changes in prostate tumorigenesis of TRAMP mice and how the cancer chemopreventive agent PEITC would impact or reverse these epigenomic-transcriptomic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Marked by the centromere, each chromosome is divided into a long arm (q) and short arm (p). High-risk NB children without MYCN gene amplification at stage IV often show an increase in the number of chromosomes 7, 12 and 17, lost of 11q and 3p alleles, and 17q gains [ 19 ]. However, no specific association between chromosome 10 and neuroblastoma has been reported.…”
Section: Discussionmentioning
confidence: 99%